2021
DOI: 10.2166/wqrj.2021.023
|View full text |Cite
|
Sign up to set email alerts
|

A review on adsorbent parameters for removal of dye products from industrial wastewater

Abstract: Industrial effluents are usually one of the major industries polluting the environment and surface water. It is estimated that the worldwide production of dyes is about 70 tons/year. To overcome this problem, innovative processes are suggested for the treatment of industrial effluents containing dyes and heavy metals. The goal of the processes is often to reduce the toxicity of these pollutants in order to meet treatment standards. Recently, great attention has been paid to innovative processes for physical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 96 publications
1
22
0
Order By: Relevance
“…[Riza et al, 2020; Jedynak et al, 2021; Zaghoul et al, 2021], but in the case of ΔH, it is only reported for nanoparticles, mesopore carbons and hydrogel [Anastopoulos et al, 2017; Jedynak et al, 2021; Riza et al, 2020] they have an endothermic nature for MB and MO, respectively, which in the obteined results are consistent with WLN.In other studies, it was determined that there is an exothermic process where modified hydroxyapatites are used as adsorbents[Guan et al, 2018], biochar from E. crassipes[Nurhadi et al, 2019], chitosan/cellulose[Xu et al, 2021], biochar with pineapple leaves[Soltani et al, 2021)] and MgAl[Zaghoul et al, 2021] this behavior is what was determined for the WLW adsorbent. In the case of the randomness of the solid/liquid interface in the…”
mentioning
confidence: 73%
“…[Riza et al, 2020; Jedynak et al, 2021; Zaghoul et al, 2021], but in the case of ΔH, it is only reported for nanoparticles, mesopore carbons and hydrogel [Anastopoulos et al, 2017; Jedynak et al, 2021; Riza et al, 2020] they have an endothermic nature for MB and MO, respectively, which in the obteined results are consistent with WLN.In other studies, it was determined that there is an exothermic process where modified hydroxyapatites are used as adsorbents[Guan et al, 2018], biochar from E. crassipes[Nurhadi et al, 2019], chitosan/cellulose[Xu et al, 2021], biochar with pineapple leaves[Soltani et al, 2021)] and MgAl[Zaghoul et al, 2021] this behavior is what was determined for the WLW adsorbent. In the case of the randomness of the solid/liquid interface in the…”
mentioning
confidence: 73%
“…Dye contains two components, that is, a dye agent and a dye enhancer. The dye agent imparts color in water, and the dye enhancer amplifies the dye agent, making the dye soluble in water and attaching to the surface . Thus, the untreated dyes draining into the water source jeopardize ecotoxicological effects .…”
Section: Introductionmentioning
confidence: 99%
“…The dye agent imparts color in water, and the dye enhancer amplifies the dye agent, making the dye soluble in water and attaching to the surface. 7 Thus, the untreated dyes draining into the water source jeopardize ecotoxicological effects. 8 Dyes also have ill effects on human health, including respiratory problems, skin irritation, itchy and watery eyes, and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these proceeds have two main limitations: production of by-products and the high cost of maintenance [ 2 , 5 , 18 ]. On the other hand, biological treatment is not effective for this type of contaminant due to the low biodegradation of dyes [ 2 , 13 , 19 , 20 , 21 , 22 ]. Adsorption has shown to have some advantages over the mentioned methods due to its high efficiency in the removal of dyes from wastewater including dilute solutions, and the absence of sediment produced in its operation [ 4 , 12 , 19 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption has shown to have some advantages over the mentioned methods due to its high efficiency in the removal of dyes from wastewater including dilute solutions, and the absence of sediment produced in its operation [ 4 , 12 , 19 , 23 , 24 , 25 , 26 ]. Different adsorbents have been synthesized for the removal of dyes from clays such as SBA-15, Bentonite, and other materials [ 2 , 4 , 17 , 27 , 28 , 29 ], up to the manufacture of activated carbon from different sources, however, there are large losses and high operating costs due to the possibility of pore blockage, hydroscoping, and incineration when using high temperatures [ 5 , 19 , 22 , 24 , 27 , 28 , 29 ]. These drawbacks have encouraged several researchers to study other cheap, abundant materials that have similar efficiency to materials synthesized by chemical processes, therefore the use of agro-industrial residues was considered, which are cheap and, easily available materials that only need a simple pretreatment and are materials with properties that can be exploited in another industry as well as being good candidates for the adsorption of various contaminants [ 8 , 12 , 14 , 19 , 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%